Design Laparoscopy Camera Vision System by Using Raspberry PI - Noor Ibrahim Bdaiwi, Ziad Tarik Ai-Dhhan, Zaid Abdulzahra Jabbar (Pakistan Journal of Medical & Health Sciences, 2022)
AIM: Design a laparoscopy camera system by using a small electronic board raspberry pi and including it with the appropriate programs to improve the doctor’s image or video while using the device, in addition to the ease of carrying the device and transporting it in the workplace or training and with an efficiency that is no less than the traditional device available. Methods: key component in this project is the 3-in-1 camera laparoscopy compatibility lens ,The light source with camera in front of the scope makes the training platform more realistic for the trainee .The design involves considering several important criteria, including the compromise with conventional one an Having enough workspace in the cameras field of view, easy Setup for users, making it more user-friendly and cost-effective for individual use by the trainee. Results: evaluation of the overall system vision qualities , measurement , color of the video and image in hospital . The paper introduces an innovative viewing system that can be combined with a traditional laparoscope and provides the surgeon with a general view of the abdominal cavity. Conclusion: Laparoscopy as a surgical technique has continue grow. The improvements to our video imaging laparoscopy system that is inexpensive, portable, and camera compact (Laparoscopy with Camera and Light (LDS) did not differ significantly from those obtained with conventional video laparoscopic.